Coal Smoke and Mortality in an Early Industrial Economy. (18th November 2017) - Beach, Brian; Hanlon, W. Walker
Abstract: Air pollution was severe in the nineteenth century, yet its health consequences are often overlooked due to a lack of pollution data. We offer a new approach for inferring local coal use levels based on local industrial structure and industry‐specific coal use intensity. This allows us to provide the first estimates of the mortality effects of British industrial coal use in 1851–60. Exploiting wind patterns for identification, we find that a one standard deviation increase in coal use raised infant mortality by 6–8% and that industrial coal use explains roughly one‐third of the urban mortality penalty observed during this period.